2020
DOI: 10.3390/molecules25030538
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effects on HL60 Human Leukaemia Cells Induced by Lavandin Essential Oil Treatment

Abstract: Recent scientific investigations have reported a number of essential oils to interfere with intracellular signalling pathways and to induce apoptosis in different cancer cell types. In this paper, Lavandin Essential Oil (LEO), a natural sterile hybrid obtained by cross-breeding L. angustifolia × L. latifolia, was tested on human leukaemia cells (HL60). Based on the MTT results, the reduced cell viability of HL60 cells was further investigated to determine whether cell death was related to the apoptotic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…After 24 h, 48 h and 72 h of treatment, the medium was removed, MTT solution (0.5 mg/mL) was added to the cells and they were incubated for 3 h in dark conditions at 37 • C. DMSO was used to solubilize the formazan crystals and the absorbance was read by Tecan Sunrise™ (Tecan Group Ltd., Männedorf, Switzerland) UV-vis spectrophotometer at 595 nm. The obtained optical density values were converted into percentage of cell viability and the data were elaborated with AAT Bioquest EC 50 Calculator (Sunnyvale, CA, USA) [19] in order to obtain the concentration at which the investigated substance exerts half of its maximal response values (EC 50 ). The values were repeated three times and reported as mean ± SD.…”
Section: Cytotoxicity Test (Mtt)mentioning
confidence: 99%
See 1 more Smart Citation
“…After 24 h, 48 h and 72 h of treatment, the medium was removed, MTT solution (0.5 mg/mL) was added to the cells and they were incubated for 3 h in dark conditions at 37 • C. DMSO was used to solubilize the formazan crystals and the absorbance was read by Tecan Sunrise™ (Tecan Group Ltd., Männedorf, Switzerland) UV-vis spectrophotometer at 595 nm. The obtained optical density values were converted into percentage of cell viability and the data were elaborated with AAT Bioquest EC 50 Calculator (Sunnyvale, CA, USA) [19] in order to obtain the concentration at which the investigated substance exerts half of its maximal response values (EC 50 ). The values were repeated three times and reported as mean ± SD.…”
Section: Cytotoxicity Test (Mtt)mentioning
confidence: 99%
“…L. angustifolia EO is used in perfumery and cosmetics and its activity on the central nervous system, as a sedative, anxiolytic and antidepressant, was also evidenced [12][13][14]. Furthermore, biological activities of EOs from Lavandula genus, such as antifungal, antibacterial, antioxidant and anticancer effects, were reported [15][16][17][18][19][20]. EO chemical composition is highly complex and it can vary considerably depending on several factors, such as the cultivation area, environmental conditions, morphological characteristics and processing techniques of the plant [21][22][23]; moreover, the chemical composition influences the way in which EOs exert their antibacterial activity [24].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning Hy cytotoxicity, EC 50 results were quite low, which revealed a very good activity. In our investigation, Hy was rich in α -terpineol and terpinen-4-ol, whose potential anticancer action, through cycle inhibition and apoptosis induction, has been demonstrated [ 67 , 68 ]. These compounds could explain the Hy cytotoxicity that has, until now, never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, also called programmed cell death, is a mechanism for the removal of unwanted and damaged cells in the maintenance of normal tissue homeostasis [ 23 25 ]. The resistance to apoptosis will cause tumorigenesis and results in cancer cells resistance to chemotherapy and radiotherapy [ 26 29 ]. In line with previous studies, our study showed that silencing LRIG2 enhanced the apoptosis of OS cell, due to the pro-apoptotic proteins increased and anti-apoptotic proteins decreased.…”
Section: Discussionmentioning
confidence: 99%